Effects of monetary policy on household finances. A review from financial inclusion and education in Colombia (2010-2019). - Ruiz - Escobar, Raúl David; Velásquez - Castañeda , Lauren Sofía (Universidad Francisco de Paula Santander, 2023)
The following article intends to analyze, based on conceptual framework and historical data of the fore mentioned statements, whether private agents behave in accordance with the theoretical frameworks of behavioral theory and how these attitudes correlate with monetary policies in regard to consumption, savings, spending, and investment decisions within households in order to identify the reasons which guides the behavior of families.